Effect of intensive training in improving older women's knowledge and support for infant vaccination in Nigerian urban slums: a before-and-after intervention study (2021)
Background: One of the strategies for improving vaccination uptake is to make communities understand the importance of immunization and this is expected to drive the demand for vaccines. Building the capacity of older women who supervise child care in Africa may improve infant vaccination in underserved communities. This study determined the impact of training of older women on their knowledge and support for infant vaccination in selected urban slum communities in Ibadan, Nigeria. Methods: This was a before-and-after study that enrolled women aged ≥35 years. They were trained with a manual and short video using participatory learning method over an 8 month period. The content of their training includes importance of immunization timeliness and completion, how vaccines work and how to be advocates and supporters of infant vaccination. Their knowledge and support for infant vaccination at baseline were compared with post training values using Student’s t test and Chi square test with the level of significance set at 5%. Results: There were 109 women with mean age 55.8 ± 11.6. they had a mean of 5.7 ± 2.1 training sessions. At the end of the training, their knowledge about infant vaccination and the support they give to it increased from 4.8 ± 3.8 to 10.7 ± 0.6, and 3.1 ± 3.5 to 8.1 ± 1.7 respectively. Those with good knowledge about infant vaccination increased significantly from 37(33.9%) to 82(82.8%), while those with good support for the same increased from 31(28.4%) to 85(85.9%). Women who were ≤ 64 years significantly had improved knowledge after the training compared to the older ones. Those with post-secondary education had better knowledge and greater support for infant vaccination at baseline. However, there was no difference in the knowledge and support for infant vaccination among the women across the different educational levels after the training. Conclusions: Participatory learning improved the knowledge about, and support for infant vaccination among older women supervising child care in these urban slum communities. Similar training may be extended to comparable settings in order to improve demand for infant vaccination.